(untitled) (Rupantaran: A Multidisciplinary Journal, 2025)
This research paper aims to develop knowledge about how women own decide on the means of production, land, capital, labor, and property, in the household level. Primary information was obtained and analyzed through interview and observation in rural areas where all mixed caste groups live together. The results of this qualitative research have been analyzed analytically and descriptively. The result of the study indicates that caste, traditional customs, and patriarchal family authority have determined women’s ownership of property and decisions. Women’s involvement in decisions regarding health care, children’s education, household expenditures, and mobility has gradually improved, especially among educated and young women. However, patriarchal social norms, unequal inheritance practices, limited economic independence, and lack of awareness hinder equitable property ownership. The study concludes that while progress of women is evident, social structural barriers has been still constrained women’s full ownership and control. Strengthening legal enforcement, increasing women’s literacy and economic opportunities, and challenging cultural biases are crucial to ensuring gender-inclusive development in rural community.